The liberator - Lettieri, Ben; Lee, Jack (Screenwriter); Thomas, Bruce (Screenwriter); Chanter, Keith; Jordan, Daniel; Improvise Films LTD; Leomark Studios (Firm) ([Essex, England] : Improvise Films LTD, 2017)
Martial arts fueled adventure as Ben Silver aka The Liberator has only a few hours to retrieve a priceless stolen antique and return it undamaged to his mysterious female client, reformed cat burglar, Melinda Page. --
Originally released as a motion picture in 2017
"The liberator will be back!"--beginning of closing credits.
Ben Lettieri, Keith Chanter, Daniel Jordan, Jessica Bayly, Daniel Cobb, Martin Wan, Richard Ellegard, Marc Tobit, Wilfried Tah, Chris Linnat-Scott.
Cinematographers, Yana Rits-Cairns, Numan Khan ; editor, Ryan Axe ; music, Ricardo Elgardo.
In English; with optional English subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed February 8, 2018)
Keywords: Action and adventure films; Martial arts films; Feature films; Internet videos; Streaming video